2020
DOI: 10.1097/ccm.0000000000004611
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxygenation After Prone Positioning May Be a Predictor of Survival in Patients With Acute Respiratory Distress Syndrome*

Abstract: Objectives: Prone position ventilation improves oxygenation and reduces the mortality of patients with severe acute respiratory distress syndrome. However, there is limited evidence about which patients would gain most survival benefit from prone positioning. Herein, we investigated whether the improvement in oxygenation after prone positioning is associated with survival and aimed to identify patients who will gain most survival benefit from prone positioning in patients with acute respiratory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 19 publications
3
34
0
3
Order By: Relevance
“…Most patients were male (79%), median age was 63 [55-69] years, and median body mass index was 28 [25][26][27][28][29][30][31] kg/m 2 . Median SAPS II and SOFA score at ICU admission were 36 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and 4 [3][4], respectively. Eighty-four % of patients were intubated and mechanically ventilated at ICU admission or during the first day in ICU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients were male (79%), median age was 63 [55-69] years, and median body mass index was 28 [25][26][27][28][29][30][31] kg/m 2 . Median SAPS II and SOFA score at ICU admission were 36 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and 4 [3][4], respectively. Eighty-four % of patients were intubated and mechanically ventilated at ICU admission or during the first day in ICU.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Non-Responders had higher driving pressure and ventilatory ratio, suggesting a higher extension of lung dysfunction and a lower efficiency of gas exchange. In the ARDS literature, several studies did not find a different mortality between Responders and Non-Responders in terms of oxygenation [26,27], while a recent study performed on ARDS, non-COVID patients, suggested that improved oxygenation after prone positioning might be a predictor of survival [35]. Also in our study performed in COVID-19 ARDS patients, we found that the mortality of O 2 -Non-Responders was significantly higher as compared to Responders (65% vs. 38%, p = 0.039).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, Non-Responders had higher driving pressure and ventilatory ratio, suggesting a higher extension of lung dysfunction and a lower e ciency of gas exchange. In the ARDS literature, several studies did not nd a different mortality between Responders and Non-Responders (24,25), while a recent study performed on ARDS, non-COVID patients, suggested that improved oxygenation after prone positioning might be a predictor of survival (32). Also in our study performed in COVID-19 ARDS patients, we found that the mortality of Non-Responders was signi cantly higher as compared to Responders (65% vs. 38%, p = 0.039).…”
Section: Discussionmentioning
confidence: 97%
“…We reviewed every patient with non-COVID ARDS treated using prone positioning while on mechanical ventilation since January 2014 until December 2020, and the cohort of these patients was used for a comparison between COVID-19 ARDS and non-COVID ARDS. Some of these patients were included in our previous study (9). First, we used the entire group of patients with non-COVID ARDS while adjusting for the between-group differences.…”
Section: Comparison With Non-covid Ardsmentioning
confidence: 99%
“…The bene cial effect of prone positioning on oxygenation has been known for decades, but whether the improvement in oxygenation is directly associated with patients' survival gain has been questionable (8). We have recently shown that the extent of improvement in the ratio of partial pressure of arterial oxygen (PaO 2 ) to the fraction of inspired oxygen (FiO 2 ) after prone positioning could be a predictor of survival of patients with ARDS (9).…”
mentioning
confidence: 99%